Removal of user fees no guarantee of universal health coverage: observations from Burkina Faso - Samia Laokri; Olivier Weil; K Maxime Drabo; S Mathurin Dembelé; Benoît Kafando; Bruno Dujardin
In theory, the removal of user fees puts health services within reach of everyone, including the very poor. When Burkina Faso adopted the DOTS strategy for the control of tuberculosis, the intention was to provide free tuberculosis care. In 2007 - 2008, interviews were used to collect information from 242 smear-positive patients with pulmonary tuberculosis who were enrolled in the national tuberculosis control programme in six rural districts. The median direct costs associated with tuberculosis were estimated at 101 United States dollars (US$) per patient. These costs represented 23% of the mean annual income of a patient's household. During the course of their care, three quarters of the interviewed patients apparently faced "catastrophic" health expenditure. Inadequacies in the health system and policies appeared to be responsible for nearly half of the direct costs (US$ 45 per patient). Although the households of patients developed coping strategies, these had far-reaching, adverse effects on the quality of lives of the households' members and the socioeconomic stability of the households. Each tuberculosis patient lost a median of 45 days of work as a result of the illness. For a population living on or below the poverty line, every failure in health-care delivery increases the risk of "catastrophic" health expenditure, exacerbates socioeconomic inequalities, and reduces the probability of adequate treatment and cure. In Burkina Faso, a policy of "free" care for tuberculosis patients has not met with complete success. These observations should help define post-2015 global strategies for tuberculosis care, prevention and control.